Intersecting lives: how place shapes reentry - Leverentz, Andrea M. (University of California Press, 2022)
Introduction -- Criminalizing disadvantage : race, class, gender, and reentry in Boston -- Bouncing and the black box of reentry's neighborhood effects -- Dorchester : returning to a "high crime" neighborhood -- The South End : returning to a "gentrified" neighborhood -- South Boston : returning to a "white" neighborhood -- Small towns, poverty, and addiction -- Conclusion -- Appendix A : methods -- Appendix B : research participants.